Production Optimization and Digital Marketing of Pumpkin Egg Roll Products: A Technology-Based Intervention at Krisna UMKM (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The "Krisna" UMKM faces challenges such as limited manual production capacity and suboptimal marketing strategies, which impact operational efficiency and market reach. This community service program aims to increase production output and sales turnover by applying appropriate technology and digital promotional strategies. The program was implemented using a Participatory Action Research (PAR) approach and service learning principles, involving business partners and students in training and mentoring on the use of semi-automatic egg roll printing machines and optimizing digital marketing through social media and online marketplaces. Within two months, daily production capacity increased from 120 to 192 boxes, exceeding the initial target of 180 boxes. Time efficiency per production cycle increased by 75%, and product quality became more consistent. On the marketing side, the digital strategy resulted in a 12.25% increase in monthly turnover, primarily through WhatsApp transactions triggered by promotional content on TikTok. The multi-channel approach proved effective in expanding market reach and strengthening the identity of local products. This initiative also encouraged labor redistribution for product diversification and a shift in business mindsets towards technology and strategic marketing. This program successfully addressed initial challenges and demonstrated an intervention model that could be replicated in other UMKMs with similar characteristics.